Produção de biodieseis etílico e metílico de pinhão manso por diferentes rotas catalíticas - Portela, Flaysner Magayver (2015)
The Jatropha curcas is an oilseed with large potential for production of vegetable oil and adjust very well to Brazilian`s climate and soil, including the region of the Caatinga. This study evaluates different forms of oil production and extraction of biodiesel from crude Jatropha curcas oil (OPMB). Extraction tests were carried out with different solvents, showing that the use of ethanol increases the process efficiency process from 36% to 39% in mass. Furthermore, the use of acid catalysis during the solvent extraction reduces the oil`s acidity from 25.93 mg KOH/g to 0.52 mg KOH/g . Using the OPMB as start material in a fractional factorial design and central composite design (CCD) to optimize the reaction conditions for production of biodiesel from Jatropha curcas (BMPM) optimized through the two-step catalysis, optimizing each step separately. In esterification (1st Step) the following variables were evaluated: Temperature (TP), Time reaction (TR), % H2SO4, Molar ratio (alcohol:oil) (RM), Alcohol type (TA) and Rotation speed (VR). The study obtained a maximum point at the central composite design (CCD), determining the best conditions to esterify the OPMB in: TP of 57.3 oC, TR of 173 minutes, 0.5% H2SO4 (w/w), RM (alcohol: oil) of 11.4: 1, methanol as TA and VR 400 rpm, producing a treaty Jatropha curcas oil (OPMT) with acidity at 0.49 mg KOH/g. Then was also optimized the transesterification reaction (2nd step) of OPMT evaluating the variables: TA, TP, RM, TA and % de KOH, obtaining a maximum yield of 97.3% under the following conditions: methanol as TA, TP 35 oC, RM of 10,0: 1, TR 49.8 minutes and 1.26% of KOH. Also are produced, heterogeneous catalysts from recyclable material, expanded polystyrene sulfonated (PSES) and sulfonated polyvinyl chloride (PVCS) that showed 0.43 and 0.32 mmol of acid groups/g, respectively. Using the heterogeneous catalysts in optimized conditions to esterify the OPMB a percentage of esterification (% E) of 93.33% for the PSES and 91.45% for PVCS. The biodiesels were prepared from OPM treated with: H2SO4, PSES and PVCS in optimized conditions, determining your physicochemical properties. The quality of the biodiesels obtained in this study was assessed by parameters established by ANP, observing that Jatropha curcas is a viable option for use as a raw material to product this biofuel.